Beta-Hydroxybutyrate: A Dual Function Molecular and Immunological Barrier Function Regulator - Qi, Jiancheng; Gan, Linli; Fang, Jing; Zhang, Jizong; Yu, Xin; Guo, Hongrui; Cai, Dongjie; Cui, Hengmin; Gou, Liping; Deng, Junliang; Wang, Zhisheng; Zuo, Zhicai (Frontiers in Immunology, 2022)
Ketone bodies are crucial intermediate metabolites widely associated with treating metabolic diseases. Accumulating evidence suggests that ketone bodies may act as immunoregulators in humans and animals to attenuate pathological inflammation through multiple strategies. Although the clues are scattered and untrimmed, the elevation of these ketone bodies in the circulation system and tissues induced by ketogenic diets was reported to affect the immunological barriers, an important part of innate immunity. Therefore, beta-hydroxybutyrate, a key ketone body, might also play a vital role in regulating the barrier immune systems. In this review, we retrospected the endogenous ketogenesis in animals and the dual roles of ketone bodies as energy carriers and signal molecules focusing on beta-hydroxybutyrate. In addition, the research regarding the effects of beta-hydroxybutyrate on the function of the immunological barrier, mainly on the microbiota, chemical, and physical barriers of the mucosa, were outlined and discussed. As an inducible endogenous metabolic small molecule, beta-hydroxybutyrate deserves delicate investigations focusing on its immunometabolic efficacy. Comprehending the connection between ketone bodies and the barrier immunological function and its underlining mechanisms may help exploit individualised approaches to treat various mucosa or skin-related diseases.